Innovations in Developing HOTS IPAS Essay Questions for Fifth Grade Elementary School Students - Wicaksono, Adyatma Nugrahsanto; Faizah, Siti; Mardhatillah, Mardhatillah (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2025)
The development of High Order Thinking Skills (HOTS) questions in Science and Social Studies (IPAS) for fifth-grade elementary students is a crucial step toward improving education quality. These questions go beyond testing memory by fostering critical, analytical, and creative thinking skills aligned with modern educational demands. Employing the 3D model (Define, Design, Develop) the study systematically develops HOTS based questions tailored to learning objectives and student needs. The process integrates cognitive levels C4-C6 of Bloom's taxonomy, emphasizing analysis, evaluation, and creation to enhance higher-order thinking. Validation results show that these HOTS-based questions are "Highly Relevant," achieving scores of 92.86% for readability and alignment with learning objectives, and 100% for critical thinking indicators. The questions are effective in encouraging students to analyze, identify, and apply concepts to real-life contexts. Additionally, they support educators in transitioning from a perception of difficulty equating to HOTS to creating meaningful yet accessible questions. This research provides valuable insights into designing HOTS questions, emphasizing simplicity, relevance to daily life, and alignment with competency objectives. It highlights HOTS questions as not merely evaluation tools but as instruments to cultivate a critical and innovative generation. Further development and feedback are encouraged to refine these approaches for broader implementation in elementary education.